Low ADAMTS13 Activity Correlates with Increased Mortality in COVID-19 Patients. (28th October 2021) - Sweeney, Joseph; Barouqa, Mohammad; Krause, Gregory; Lugo, Jesus Gonzalez; Rahman, Shafia; Reyes, Morayma
Abstract: Systemic inflammation and coagulopathy are characteristic hallmarks of COVID19. "COVID coagulopathy" manifests mainly as a prothrombotic state affecting both large and small blood vessels, and presenting as arterial, venous, and microangiopathic thrombotic events with von Willebrand factor (VWF) and soluble thrombomodulin increased in hospitalized patients. The causes of coagulopathy are poorly understood. Aim: To investigate the relationship between von Willebrand factor (VWF) biomarkers, intravascular hemolysis, coagulation, and organ damage in COVID19 patients and to study their association with disease severity and mortality. Methods: 181 hospitalized adult COVID19 patients were randomly selected with a balanced distribution of survivors and non-survivors during the period of March 26 th 2020 to May 5 th 2020. The medical records and laboratory values were reviewed. Statistical analysis was performed using R studio V.3.6.2. Results: Patients who died (n=90) had significantly lower ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) activity, elevated lactate dehydrogenase levels, increased schistocyte/RBC fragment counts, and elevated VWF antigen and activity levels compared to patients discharged alive (n=91). In 31 patients, we measured several of these biomarkers on two or more occasions. The trending of ADAMTS13 activity illustrated that it is not steady throughout the hospitalization course. ADAMTS13 activity levels tended to improve and/or reach normal levels in patients that survived, yet ADAMTS13 activity levels worsened in most patients that died. Likewise, the VWF antigen and activity levels tended to decrease in patients that survived whereas tended to increase well above the normal range (2-3 folds) in patients that died. D-Dimer levels trended downwards in survivors, sometimes to levels less than 1 µg/ml, yet tended to increase in patients who died. Given the relationship between ADAMTS13 activity and mortality, we wanted to determine a cut-point of initial ADAMTS13 activity (within 72 hours from admission) to predict mortality. 102 patients in our cohort had an ADAMTS13 activity measurement within this timeframe. We determined that this optimal cut-point of initial ADAMTS13 activity was 43% using Youden's J statistic. Only 30% of patients who had an ADAMTS13 activity level of less than 43% on admission survived, yet 60% of patients survived who had an ADAMTS13 activity level of greater than 43% on admission. Conclusions: COVID-19 may present with low ADAMTS13 activity in a subset of hospitalized patients. Presence of schistocytes/RBC fragment and elevated D-dimer levels on admission may warrant a work-up for ADAMTS13 activity and VWF antigen and activity levels. These findings indicate the need for future investigation to study the relationship between endothelial and coagulation activation and the efficacy of treatments aimed at prevention and/or amelioration of microangiopathy in COVID-19.